Campaign promises as an imperfect signal: How does an extreme candidate win against a moderate candidate?. (October 2015) - Asako, Yasushi
This study develops a political competition model in which campaign platforms are partially binding. A candidate who implements a policy that differs from his/her platform must pay a cost of betrayal, which increases with the size of the discrepancy. I also assume that voters are uncertain about candidates' policy preferences. If voters believe that a candidate is likely to be extreme, there exists a semi-separating equilibrium: an extreme candidate imitates a moderate candidate, with some probability, and approaches the median policy with the remaining probability. Although an extreme candidate will implement a more extreme policy than a moderate candidate, regardless of imitation or approach, partial pooling ensures that voters prefer an extreme candidate who does not pretend to be moderate over an uncertain candidate who announces an extreme platform. As a result, a moderate candidate never has a higher probability of winning than an extreme candidate.